Aplikasi Sistem Informasi Manajemen Aset Berbasis Web - Rizki Rahmadia Putra; Ramanda Nur Ikram; Perdana, Erda Guslinar (Journal of Applied Engineering and Social Science (JAESS), 2025)
Management plays an important role in a person's life by helping to achieve goals, reduce costs and effort, and provide direction and stability. Asset management is a crucial part of maintaining financial and economic stability, as assets are wealth that can serve as future security. Property, as one form of investment, can generate income through buying and selling at a higher price. However, many companies face challenges in managing assets efficiently. Therefore, we developed an asset management platform called Goopro, which focuses on asset management and transactions to help companies optimize their resources. In its development, Figma is used as a tool for interface design, while Google Forms is used for data collection needed in the application development process. The technologies applied include the Laravel framework for application development and MySQL as the database. This platform is expected to provide an effective solution for organizing and managing assets, supporting the economic growth of both companies and individuals.